Potential tuberculostatic agents. Topliss application on benzoic acid [(5-nitro-thiophen-2-yl)-methylene]-hydrazide series - Rando, D. G.; Sato, D. N.; Siqueira, L.; Malvezzi, A.; Leite, CQF; do Amaral, A. T.; Ferreira, E. I.; Tavares, L. C. (Elsevier B.V., 2002)
Nitroaromatic compounds such as nifuroxazide are used in many human enteropathogenic bacteria infections without causing an increase in the plasmidial antibiotic resistance of the aerobic Gram-negative intestinal Enterobacteriaceae. For these reasons, these compounds have been synthesized using the rational approach of Topliss' decision tree. Generally. this approach allows us to obtain the most active derivative from the series in a few steps. These compounds were tested against Mycobacterium tuberculosis in vitro and the most active of the series identified. A new lead for potential tuberculostatic activity has been predicted and will be used in further QSAR studies. (C) 2002 Elsevier B.V. Ltd. All rights reserved.